The quasi-static behavior of hybrid corrugated composite/balsa core sandwich structures in four-point bending: Experimental study and numerical simulation. (1st May 2020) - Sayahlatifi, Saman; Rahimi, G.H.; Bokaei, Alireza
Highlights: The introduction of the corrugated composite to the balsa core suppresses catastrophic failure. The proposed hybrid core rises strength and stiffness of the sandwich structure, although it has a negligible effect on specific stiffness under four-point bending. Rectangular-shaped corrugation results in a surpassing performance. The proposed hybrid core sandwich beam indicates structural preponderance in terms of both strength and stiffness, as weight is considered as a design parameter. Abstract: This study aims to investigate the effect of the insertion of a corrugated composite into the typical balsa core sandwich structure under four-point bending (FPB). The proposed sandwich structure is composed of aluminum face sheets, balsa wood with an average density of 125 kg/m 3 and E-glass woven fabric. For obtaining full-field strains and deflection distribution, a digital image correlation (DIC) technique was employed. Based on continuum damage mechanics (CDM), a three-dimensional finite element model (FEM) was developed to predict the ultimate load-bearing capacity and failure mechanisms of the sandwiches. To this end, the material damage models for balsa wood and corrugated composite were implemented in ABAQUS software via VUMAT subroutine. After validating the numerical model, the effect of geometric parameters of the corrugated composite on the response of the sandwich structure was explored numerically. The findings demonstrated that the proposed hybrid core not only prevents catastrophic failure but also increases weight-specific strength by 38.4%. However, it appears that the hybrid core has no significant influence on the weight-specific stiffness under FPB. The parametric study showed that with increasing the corrugation angle and thickness, the specific strength/stiffness exhibits an ascending trend. Moreover, rectangular-shaped corrugation contributed to the best mechanical performance.